PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE (SSCS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DI SMA NEGERI 4 KAUR - Melisa Antasari; Hanifah Hanifah; Agus Susanta; Saleh Haji (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of the Search, Solve, Create and Share (SSCS) model on Problem Solving and creative thinking skills. This type of research is a quasi-experiment. The population of this study were all students of class XI MIA SMA Negeri 4 Kaur. The instrument of this research is a test of mathematical problem-solving ability and mathematical creative thinking ability. The results showed that there were: (1) the linear effect of initial ability covariates on students' problem-solving abilities with an effect of 7.9%. (2) the linear effect of initial ability covariates on students' mathematical creative thinking abilities with an effect of 42.9%. (3) the linear effect of initial ability covariates on students' mathematical creative thinking abilities with an effect of 42.9%. (4) the effect of using the SSCS learning model on students' problem-solving abilities by 7.7%. (5) the achievement of problem-solving abilities of class XI MIA SMAN 4 Kaur students who were taught using the SSCS learning model was higher than classes taught by conventional learning models. (6) the achievement of creative thinking abilities of class XI MIA SMAN 4 Kaur who were taught using the learning model SSCS is higher than classes taught by conventional learning models